1999
DOI: 10.1002/(sici)1097-4628(19990912)73:11<2187::aid-app16>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Photograft copolymerization of methyl methacrylate on silk fiber using titanium(III) chloride-potassium persulphate redox initiator in a limited aqueous system. I

Abstract: Graft copolymerization of methyl methacrylate (MMA) onto mulberry silk fibers has been investigated in a limited aqueous system employing titanium(III) chloride-K 2 S 2 O 8 as the redox initiator under a photoactive condition with visible light. Polymerization in the presence of light at 32 Ϯ 1°C has been found to be more pronounced than in the dark under identical conditions. The percentage of grafting, the percentage of total conversion, and the percentage of grafting efficiency have been studied by varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Graft copolymerization of RWF with various MA concentrations was carried out at 50 °C for 1 h. It was observed that the degree of grafting increased as the monomer amount was increased in the grafting reaction, and reached 187% at 0.05 mol of MA, as shown in Fig 7. The increase of grafting percentage could be due to the increase in grafting rate22 and the gel effect 23…”
Section: Resultsmentioning
confidence: 99%
“…Graft copolymerization of RWF with various MA concentrations was carried out at 50 °C for 1 h. It was observed that the degree of grafting increased as the monomer amount was increased in the grafting reaction, and reached 187% at 0.05 mol of MA, as shown in Fig 7. The increase of grafting percentage could be due to the increase in grafting rate22 and the gel effect 23…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the degree of grafting increased as the monomer amount was increased in the grafting reaction, reaching 82.4% at 2.36 × 10 −2 mol of MMA, as shown in Figure 5. The increase of grafting percentage may be a consequence of the increased grafting rate19 and the gel effect 20…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the solvents do not have much of an affect on the fiber orientation before and after have grafting. Whenever the grafting reaction is conducted in their presence, the tenacity remains almost unchanged because it is a function of the fiber orientation 11…”
Section: Resultsmentioning
confidence: 99%